2022
DOI: 10.1371/journal.pgen.1010034
|View full text |Cite
|
Sign up to set email alerts
|

MxB inhibits long interspersed element type 1 retrotransposition

Abstract: Long interspersed element type 1 (LINE-1, also L1 for short) is the only autonomously transposable element in the human genome. Its insertion into a new genomic site may disrupt the function of genes, potentially causing genetic diseases. Cells have thus evolved a battery of mechanisms to tightly control LINE-1 activity. Here, we report that a cellular antiviral protein, myxovirus resistance protein B (MxB), restricts the mobilization of LINE-1. This function of MxB requires the nuclear localization signal loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 79 publications
(139 reference statements)
0
6
0
Order By: Relevance
“…Immunofluorescence and immunogold labeling show that ORF1p accumulates in LBs at exceptionally high levels (this work and 46 ). Prior studies in cultured cells have reported L1 association with SGs and their contribution to cellular defenses against L1 17,37,38,[76][77][78] . Meanwhile, L1 localization to PBs was reported only sporadically 79 .…”
Section: Discussionmentioning
confidence: 98%
“…Immunofluorescence and immunogold labeling show that ORF1p accumulates in LBs at exceptionally high levels (this work and 46 ). Prior studies in cultured cells have reported L1 association with SGs and their contribution to cellular defenses against L1 17,37,38,[76][77][78] . Meanwhile, L1 localization to PBs was reported only sporadically 79 .…”
Section: Discussionmentioning
confidence: 98%
“…Immunofluorescence and immunogold labeling show that ORF1p accumulates in LBs at exceptionally high levels (this work and [45]). Prior studies in cultured cells have reported L1 association with SGs and their contribution to cellular defenses against L1 [17,36,37,[78][79][80]. Meanwhile, L1 localization to PBs was reported only sporadically [81].…”
Section: Discussionmentioning
confidence: 99%
“…Given the function of ZAP in the destabilization of L1 RNAs and retrotransposition events, SG might be the cellular compartment involved in RNA metabolism to limit the stability of L1 RNAs and/or inhibit translation. Myxovirus resistance protein B (MxB), another interferonstimulated gene, also restricts L1 retrotransposition by enhancing the sequestration of ORF1p to G3BP1-containing cytoplasmic granules [105]. As MxB inhibits the nuclear import of HIV-1 and herpesvirus [106], the sequestration of L1 RNPs into SG might prevent the accession of L1 RNPs to the nucleus for their reverse transcription.…”
Section: Stress Granule (Sg) and Te Regulationmentioning
confidence: 99%